The development of Flanatomy as a learning media for ADHD students based on a 3D puzzle and augmented reality - Hariadi, Bambang; Erdiana, Setya Putri; Masitoh, Siti; Sagirani, Tri; Efendi, Wawan Wahyudi; Prasetyo, Tegar (Edelweiss Applied Science and Technology, 2025)
ADHD students have low concentration and face significant challenges in engaging in cognitive activities. Therefore, it is necessary to utilize concrete and engaging learning media that meet their needs and characteristics. The goal of this study is to develop Flanatomy, a learning media that integrates 3D puzzles with augmented reality technology. This research is categorized as Research and Development (R&D) using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The study employed research instruments such as questionnaires and interviews. The feasibility of the Flanatomy product was assessed through validation by subject matter experts, who gave an average score of 3.37; learning media experts, with an average score of 3.6; and design experts, using the User Experience Questionnaire (UEQ), which indicated an average score above 0.8, classified as highly feasible. Practicality testing showed that the product is highly practical and easy to use, with validation from teachers at SLB Putra Mandiri Surabaya as users, who provided an average score of 3.48. Based on these results, the Flanatomy product is deemed highly feasible and practical for use as a learning medium for ADHD students.